Presence of low-grade IPMN at the pancreatic transection margin does not have prognostic significance after resection of IPMN-associated pancreatic adenocarcinoma. Issue 1 (January 2023) - Leonhardt, Carl-Stephan; Hinz, Ulf; Kaiser, Jörg; Hank, Thomas; Tjaden, Christine; Bergmann, Frank; Hackert, Thilo; Büchler, Markus W.; Strobel, Oliver
Abstract: Introduction: Resection margin status is a well-established prognosticator in pancreatic cancer. The prognostic impact of IPMN dysplasia at the pancreatic transection margin in IPMN-associated carcinoma (IPMN-Ca) remains unclear, hence institutional practices on additional resections vary. Methods: Patients undergoing partial pancreatectomy or attempted partial pancreatectomy converted to total pancreatectomy for IPMN-Ca between 04/2002 and 12/2018 were identified. Final pathology of the definitive pancreatic transection margin was identified. The association between the presence of IPMN dysplasia at the margin and overall survival (OS) was assessed. Results: Of 302 patients with IPMN-Ca, 181 (59.9%) patients received partial pancreatoduodenectomy, 61 (20.2%) distal pancreatectomy, and 60 (19.9%) were converted to total pancreatectomy. Median OS was 98.6 months in R0 (≥1 mm), 39.3 months in R1 (<1 mm), and 22.0 months in R1(direct) resected patients, respectively (p < 0.0001). No IPMN dysplasia at the definitive margin was present in 103 (34.1%), low-grade in 131 (43.4%), and high-grade/R1 in 8 (2.6%) patients. Low-grade dysplasia or total pancreatectomy were not associated with shorter OS compared to dysplasia-free margin across the entire cohort. Sensitivity analyses confirmed a lack of prognostic relevance of low-grade IPMN dysplasia at the pancreatic margin in R0 resected IPMN-Ca and in R0 resected UICC stage IA/IB IPMN-Ca. Conclusions: Low-grade IPMN at the transection margin is not associated with shorter overall survival after partial pancreatectomy for IPMN-Ca. Additional resections for low-grade dysplasia, up to total pancreatectomy do not result in a survival benefit and should be omitted. Due to limited sample size, high-grade dysplasia could not be analyzed.